(untitled) (Global Journal of Management and Business Research, 2019)
Libraries and information centers are service units held with the responsibility of providing varied information services based on a number of resources. It covers tangible assets, namely library building, equipment, furniture, information resources and staff. The intangible element has been the information services provided by the libraries. The tangible assets and intangible services of libraries are changing greatly due to the development and changes in the area of information technology. Libraries may not be the first thing that comes to mind when thinking about great design. It#x2019;s easy to assume the user experience of a library is limited to navigating a maze of bookshelves in reality; there has been a recent push among librarians and library professionals to apply userexperience best practices to the design of their services. Library UX professionals include librarians and library staff members who specialize in improving the user experience of their libraries through research and design.